Teachers, schools, and society : - Sadker, David Miller (McGraw-Hill, 2011)
Combining the brevity of a streamlined Introduction to Education text with the support package of a much more expensive book, the brief edition of Teachers, Schools, and Society encourages experienced instructors to explore their own creativity while ensuring that newer faculty can teach the course with confidence. David Sadker’s and Karen Zittleman’s lively writing style captures the joys and challenges of teaching. The text stresses the importance of fairness and justice in school and society, focuses on the most crucial topic areas, and integrates the most current issues in education. In addition, the wealth of activities included--from online video observations to portfolio-building exercises--offers a broad range of ways to introduce students to the teaching profession.